UPAYA SATLANTAS POLRESTA SURAKARTA DALAM MENCEGAH KECELAKAAN LALU LINTAS DI PERSIMPANGAN GENENGAN - MUHAMMAD FADLI (Indonesian Journal of Police Studies, 2022)
ABSTRACT EFFORTS OF THE SURAKARTA TRAFFIC UNIT TO PREVENT TRAFFIC ACCIDENTS AT GENENGAN INTERSECTION MUHAMMAD FADLI, 18.112, mfadli132@gmail.com The research in this final project focuses on preventing traffic accidents at the Genengan intersection. This research was conducted because accidents often occur at the Genengan intersection every year. The location is also considered an accident-prone area because it has claimed lives. Therefore, the author wants to know how the efforts made by the Surakarta Police Traffic Unit in preventing traffic accidents at the Genengan intersection. In accordance with Law No. 22 of 2009 concerning road traffic and transportation and the Implementation Instructions of the National Police Chief No. Pol: Juklak/05/V/2003 concerning traffic education. The purpose of this study is to describe how the implementation of the Surakarta Police Traffic Unit in preventing traffic accidents at the Genengan intersection and to describe how the efforts of the Surakarta Police Traffic Unit in preventing traffic accidents at the Genengan intersection. This study uses a qualitative approach with field studies so that the authors can directly obtain data from interviews and observations. In the conceptual literature to analyze the problems that occur, the researcher uses the concept of traffic, the concept of traffic accidents, and the concept of prevention. Meanwhile, the theory used is the management theory of George R Terry and the SWOT Analysis Theory. Data was collected by means of interviews, observation, and document review. Based on the discussions and findings in the field, there are still shortcomings in the efforts to prevent traffic accidents at the Genengan intersection carried out by the Kamsel Unit. It can be concluded that the implementation of community education activities is more focused on preventing the Covid-19 pandemic, community education activities are carried out more on organized communities, public address activities are not effective because they are only carried out in the city. In addition, there are also internal and external factors that hinder efforts to prevent traffic accidents at the Genngan intersection. Keywords:Prevention, effort, Genengan.